Report of the joint committee relative to conscription of state officers by the Confederate government : March 4, 1864 (Document (Virginia. General Assembly. Senate), 1864)
1864 Report of the Joint Committee regarding the conscription of state officers by the Confederate government. The committee recommended resolution of the governor's request that certain enumerated officials be exempt from this conscription as vital to the state's needs and security.